The SEKOPER Program: Informal Women’s School Implemented by the PUG–PHA Division, DP3APPKB Surabaya City - Valentina Yosephin Angel Puspita; Siti Jaro'ah (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study explores the implementation of the SEKOPER (Sekolah Perempuan Informal) program by the Department of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3APPKB) of Surabaya City. Employing a qualitative observational approach based on internship experience, the research focused on program delivery in multiple subdistricts between April and June 2025. Observational data were supported by informal interviews and document reviews, with analysis guided by the Street-Level Bureaucracy theory (Tummers & Bekkers, 2021) and Social Capital theory (Putnam, 2020; Woolcock & Narayan, 2022). Findings indicate that the participatory and contextual design of the SEKOPER program effectively empowers women heads of households from underprivileged backgrounds through practical training such as cooking and beauty classes. These initiatives not only build individual capacity but also create sustainable economic opportunities. The program’s success is reinforced by inclusive social interactions between organizers and participants, along with strong support from local government. However, institutional strengthening and program expansion are recommended to enhance impact and sustainability. This research contributes to discussions on micro-level policy adaptation and the role of social capital in the success of community empowerment programs.